Adaptação do método de multiplicação rápida, relações entre caracteres e amostragem na produção de mudas, ramas e raízes de mandioca - Schöffel, André (2019)
The aim of this research was to evaluate an adaptation of the rapid multiplication method, to improve management techniques during propagation, seedling production and field cultivation for cassava stems and roots production, as well as to study the correlations between groups of traits and determine the sample size for traits in the stages of the production process. Three experiments were conducted in the 2017/2018 crop to evaluate the use of Apronta Mesa stem cuttings in two diameter intervals: 15 to 19.99 mm (lower than 20 mm) and 20 to 25 mm (higher than 20 mm) at five planting seasons (June, July, August, September and October) for cuttings production (experiment 1); to evaluate the characteristic for cuttings collection (number of leaves) for seedling production in four planting seasons (September 22, October 7 and 19, and November 25) (experiment 2); and to evaluate the yield of stems and roots in different spacings in four transplantation seasons of seedlings (November 9 and 24 and December 3 and 26) (experiment 3). Still, the relationships between the traits of the groups: stem cutting, seedling, stem and root were identified through the canonical correlation and the sample size was determined for the estimation of the average of the traits measured in the seedlings and the productivity of stems and roots. The use of stem cuttings between 20 and 25 mm in diameter should be prioritized for producing cassava seedlings. The cuttings should be collected with 6 to 8 visible leaves and planted at the end of September. Seedling transplantation performed up to November 24 favored the expression of stems and root yield traits. Higher plant heights at planting and transplantation favored root yield traits. For traits measured in seedling yield and stems and roots yield of 63 and 153 plants, respectively, are sufficient to estimate the mean when the 95% confidence interval amplitude was equal to 20% of the mean estimate.